Distribution and accumulation of chlorobenzenes in vegetables - ZHANG Jian-ying; ZHAO Wei; PAN Jun; QIU Li-min; ZHU Yin-mei (浙江大学学报. 农业与生命科学版)
Five seasonal vegetables and the soils in three different districts were investigated with respect to levels of chlorobenzenes (CBs), including 1,2-DCB (o-DCB), 1,3-DCB (m-DCB), 1,4-DCB(p-DCB), 1,2,4-TCB. The partition relationship in different parts of vegetables was analyzed and the partition-limited model was used to explain the bioaccumulation of CBs by vegetables. As shown by our result, m-DCB and 1,2,4-TCB, which have relatively low molecular weight, were the predominant CBs in vegetables. The accumulation of CBs in spinach (Spinacia oleracea), Chinese cabbage (Brassica rapavar. pekinensis), and celery (Apium graveolensvar. dulce), expressed as concentration of CBs in discending order was root > leaf > stem. While in radish (Raphanus sativus) and carrot (Daucus carota subsp. sativus) it was leaf > stem > root. This was suitable for the partition-limited model, and this implied that root was the main pathway thorugh which CBs enter vegetable plants and the accumulation was well related with Kow, the lipid content of the vegetable.